A novel single-stage ceramic membrane moving bed biofilm reactor coupled with reverse osmosis for reclamation of municipal wastewater to NEWater-like product water. (April 2021) - Sun, Huifang; Liu, Hang; Zhang, Meng; Liu, Yu
Abstract: In this study, a single-stage ceramic membrane moving bed biofilm reactor (CMMBBR) was developed for simultaneous COD and nitrogen removal, while its effluent was further reclaimed to ultra-clean water by a coupled reverse osmosis (RO) unit. Results showed that approximately 97% of COD and 93% of total nitrogen (TN) removal were obtained in CMMBBR, with the effluent COD and TN concentrations being 8.15 mg/L and 2.31 mg/L, respectively. The excellent performance of CMMBBR was achieved at a constant permeate flux of 30 L/m 2 /h (LMH), with the average dTMP/dt of 0.05 bar/d due to the low suspended sludge concentration (i.e. 75 mg VSS/L) and the effective membrane scouring by fluidized biocarriers. The excellent permeate quality of CMMBBR could lead to a very low RO fouling rate of 0.029 bar/d, with the product water quality meeting typical NEWater standards in major ions concerned. In addition, the energy and cost analyses further indicated that the proposed CMMBBR-RO process could reduce 43.8% of energy consumption and 23.5% of operating cost compared to the current NEWater production process. It is expected that the integrated CMMBBR-RO process could provide a promising alternative for municipal wastewater reclamation to high-grade product water towards minimized sludge production and energy-efficient operation. Graphical abstract: Image 1 Highlights: 97% and 93% of COD and TN were simultaneously removed in CMMBBR. Scouring by carriers prevented membrane fouling, leading to a flux of 30 LMH. Product water of CMMBBR-RO could meet the typical NEWater standards. CMMBBR-RO process could be modularized for easy scaling-up or down. Reduced energy consumption and operating cost were achievable in CMMBBR-RO process.